2014
DOI: 10.1097/mao.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Traumatic Stapediovestibular Luxation

Abstract: In patients with pneumolabyrinth after middle ear trauma with mild symptoms, we recommend initial conservative treatment with close monitoring of hearing. In patients with severe, persisting, or progressive vestibulocochlear symptoms, exploratory tympanotomy should be performed to check for and treat PLF. Oval window fistula repair is reported to have variable hearing outcomes but offers complete resolution of vestibular symptoms in most cases. The stapedial strut is one of the possible surgical techniques in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Since the stapes’ location deep in the tympanic cavity normally protects it from external trauma, stapediovestibular dislocation is rare. In a recent study of stapediovestibular dislocation, most cases showed internal dislocation (depressed into the vestibule) and external dislocation was uncommon [ 4 ]. An internal dislocation can be caused by direct penetrating injury by cotton swabs or ear-pick, and external dislocation can occur when the annular ligament is torn by traumatic force.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the stapes’ location deep in the tympanic cavity normally protects it from external trauma, stapediovestibular dislocation is rare. In a recent study of stapediovestibular dislocation, most cases showed internal dislocation (depressed into the vestibule) and external dislocation was uncommon [ 4 ]. An internal dislocation can be caused by direct penetrating injury by cotton swabs or ear-pick, and external dislocation can occur when the annular ligament is torn by traumatic force.…”
Section: Discussionmentioning
confidence: 99%
“…The patient might have had sensorineural hearing loss or severe dizziness, suggestive of PLF at the time of accident, but he had no memory of vestibulocochlear symptoms, possibly precluding a PLF. Management of stapediovestibular dislocation depends on the integrity and position of the stapes as well as the preoperative hearing status [ 4 ]. In cases in the literature, stapediovestibular dislocation was treated by various surgical methods, the most common of which was ‘stapes repositioning and sealing’ or stapedotomy/stapedectomy, and overall the hearing results were reported to be good [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stapediovestibular luxations are rare lesions that are most commonly caused by direct and penetrating trauma to the external ear canal [ 19 , 20 ], though they have also be associated with incudomalleolar disarticulation and stapes fracture [ 21 ]. The footplate can also be dislocated in the tympanic cavity due to a traumatic force tearing the annular ligament via an increase in perilymphatic pressure (external dislocation) [ 22 ].…”
Section: External and Middle Earmentioning
confidence: 99%